Concomitant Detrusor and External Urethral Sphincter Botulinum Toxin-A Injections in Male Spinal Cord Injury Patients with Detrusor Overactivity and Detrusor Sphincter Dyssynergia - Yu-Hui Huang; Sung-Lang Chen (Medical Journals Sweden, 2022)
Objective: To investigate the effects of concomitant injections of botulinum toxin-A (BoNT-A) into the detrusor and external urethral sphincter muscles in suprasacral spinal cord injured patients with detrusor overactivity and detrusor sphincter dyssynergia. Design: An open treatment trial with pre- and posttreatment evaluations. Subjects: Male suprasacral spinal cord injury patients (n = 20) with neurogenic detrusor overactivity and detrusor sphincter dyssynergia who emptied their bladder by reflex voiding and were unwilling to increase the frequency of intermittent catheterization. Methods: Cystoscopic guidance of 200 U BoNT-A injections into the detrusor muscle and 100 U into external urethral sphincter muscles were applied. The urodynamic parameters, voiding diaries and quality of life scores using Urinary Distress Inventory, Short Form (UDI-6) and Incontinence Impact Questionnaire, Short Form (IIQ-7) were compared. Results: All participants experienced a significant mean reduction in maximal detrusor pressure and maximal urethral pressure profile, and a mean significant increase in maximal cystometric bladder capacity 12 weeks after concomitant injections. Bladder diaries demonstrated persistently increased spontaneous voided volume, but no increase in post-void residual ratio, daily clean intermittent catheterization (CIC) frequency and diaper pad use from baseline to 24 weeks. UDI-6 scores were significantly improved at 4 and 12 weeks and IIQ-7 scores improved only at 12 weeks. Conclusion: Concomitant detrusor and external urethral sphincter BoNT-A injections may decrease detrusor and urethral pressure without increasing postvoid residual ratio and diaper pad use. For spinal cord injury patients with neurogenic detrusor overactivity and detrusor sphincter dyssynergia who are unwilling, or for whom it is inconvenient, to increase CIC frequency and who want to preserve spontaneous voiding, this treatment may provide an optional alternative. LAY ABSTRACT Detrusor botulinum toxin type A (BoNT-A) injection has become the standard of care for bladder overactivity associated with neurological pathology in recent years. However, increased post-void residual and even acute urinary retention make it difficult for patients to accept this treatment. Our study demonstrates that a combination of detrusor and urethra sphincter BoNT-A injections may relieve detrusor and urethral pressures without increasing intermittent catheterization (IC) frequency. Life quality associated with voiding is also improved after combined injections. Physicians should take into account the patient's expectation and ability to manage his bladder when planning BoNT-A injection in treatment of neurogenic lower urinary tract dysfunction (NLUTD) in spinal cord injury (SCI) patients. For male SCI patients with NLUTD who are unwilling or inconvenient to increase IC frequency and want to preserve spontaneous voiding, this treatment may provide optional alternative.